Toward an Improved Multi-Criteria Drug Harm Assessment Process and Evidence-Based Drug Policies - Dubljević, Veljko (Frontiers in Pharmacology, 2018)
Drug scheduling within the international system of drug control and national legislation has been recently criticized as having insufficient footing in scientific evidence. The legal harms related to non-medical uses of certain drugs (e.g., cannabis) have arguably exceeded their physiological and social harmfulness compared to legally available substances (e.g., tobacco), which prompted some states to explore alternative regulation policies, similar to the drug regime in the Netherlands. Other legally prescribed drugs (e.g., stimulants) created a surge of interest for “better than well” uses, while yet others (e.g., opioids) caused an epidemic of dramatic proportions in North America. The evidence-based Multi-Criteria Drug Harm Scale (MCDHS) has been proposed as a way of grounding policy in the actual degree of harmfulness of drugs. Indeed, the scale has had great ramifications in several areas of policy, and it has been used extensively in distinct lines of interdisciplinary research. However, some aspects of MCDHS remain disputed. For example, the way the data has been generated has been criticized as suffering from "expert bias.” This article reviews strengths and weaknesses of evidence provided with the use of MCDHS. Furthermore, the author argues that the shortcomings of MCDHS can be resolved by offering methodological improvements. These include 1) dissociating the harms of use from harms of abuse, 2) adding the perspectives of people who use drugs, pharmacists, and general medical practitioners along with the expert assessments, and 3) focusing on subsets of drugs to allow for comparison without mixing different social contexts of drug use. The paper concludes with outlines of substance subset-specific extensions of the MCDHS and related policy proposals in the four areas identified as generating the most controversy: nonmedical use of opioids, "study aid" uses of stimulants, shifting trends in nicotine containing products, and regulation of medical and recreational uses of cannabis.